Kriminalisasi Homoseksual Sebagai Tindak Pidana: Studi Determinasi Moral Sebagai Hukum Pidana - Sholihin, Riadhus; Rahma, Rahma; Zubaidi, Zaiyad (STAINI Press, 2023)
This study discusses the criminalization of homosexuality as a crime. This research is motivated by cases of homosexuality which are increasingly being discussed in Indonesia until now homosexuals have the courage to demonstrate their deviations from their sexual orientation in public. This study focuses on the problem of how moral determination is in criminal law and whether homosexuality committed by adults can be used as a crime. This research method is qualitative. The results of the study show that there is a very close relationship between morals and criminal law, therefore the basis of morality in criminal law is an important issue. In determining criminal acts, the moral system must be considered. Even though there is no obligation, the morality of society must at least be paid close attention to by the state when determining an act as a crime. Based on the moral theory, the policy of criminalizing homosexual acts fulfills the criteria of criminalization, that is, the act is immoral and harmful to individuals and society. Homosexual acts committed by same-sex couples need to be made criminal acts, first: Juridical basis, based on Law Number 11 of 2012, Pancasila and several articles in the NRI Constitution and finally Article 1 paragraph (1) of the Criminal Code which regulates the principle of legality. Second: philosophical basis, it is realized that the criminalization of homosexual acts against homosexual acts committed by same-sex couples meets the general criteria for criminalization which is supported by forms of criminalization theory: moral theory, Feinberg theory and paternalism theory. Third: sociological basis, homosexual acts of the same sex as an act that is not in line with the soul, nation, the reaction of the community that rejects homosexual activity, and is not in line with the style of customary law society.